2017
DOI: 10.1136/tobaccocontrol-2017-053944
|View full text |Cite
|
Sign up to set email alerts
|

To sell or not to sell: cigarette sales in alcohol-licenced premises

Abstract: Despite claims by tobacco companies that tobacco sales are important for many Australian retailers, tobacco sales appear to be of limited importance for alcohol-licenced premises. This means that opposition to stopping tobacco sales where alcohol is consumed and/or sold may be less than expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…First, retailers where the decision to sell is likely to be made at a head office level (ie, large supermarkets, chained 7-Eleven type stores and petrol (gas) stations and any stores located within those petrol stations) were excluded. Second, alcohol licensed outlets were excluded in NSW, since they had previously been surveyed in a comparable study 11. The sampling method has been published elsewhere,12 but is summarised here.…”
Section: Methodsmentioning
confidence: 99%
“…First, retailers where the decision to sell is likely to be made at a head office level (ie, large supermarkets, chained 7-Eleven type stores and petrol (gas) stations and any stores located within those petrol stations) were excluded. Second, alcohol licensed outlets were excluded in NSW, since they had previously been surveyed in a comparable study 11. The sampling method has been published elsewhere,12 but is summarised here.…”
Section: Methodsmentioning
confidence: 99%
“…This study included a national database of tobacco retailers, excluding retailers with an on-license. Australian research found approximately 60% of hotels and clubs sold tobacco, 44 so our study is likely to have underestimated the impact of these policies. It was beyond the scope of this study to physically verify the sale of tobacco in each store; however, online and phone auditing was undertaken.…”
Section: Discussionmentioning
confidence: 83%
“…11 It is also known the characteristics of the location of cigarette sales, motivation and selling the power of wholesalers, retail as well as the cigarette promotion media, increase cigarette purchases by the public and young people groups. 12 Mulawarman University is one of the universities in Samarinda, East Kalimantan with an active smoker (22.3%). 13 Mulawarman University is a university with the largest number of students in Kalimantan, reaching more than 37,000 people.…”
Section: Introductionmentioning
confidence: 99%